A Novel CMOS OTA Based on Body-Driven MOSFETs and its Applications in OTA-C Filters - Xuguang Zhang, Xuguang Zhang; El-Masry, E.I (IEEE transactions on circuits and systems. I, Regular papers, 2007)
The operational transconductance amplifier (OTA) is one of the most significant building-blocks in integrated continuous-time filters. Traditional OTAs suffer linearity reduction as a result of the MOSFET scaling trend. In this paper, a body-driven (BD) CMOS triode-based fully balanced OTA is proposed to achieve low distortion and linear frequency tuning. In contrast to the gate-driven based OTAs (that have the tradeoff of input and tuning range), BD-based OTAs operate under a wide input range over a large tuning interval. Common-mode (CM) feedforward and CM feedback schemes have been developed so that the CM voltage varies only 7 mV over a tuning range of 1.2 V = Vtune = 1.58 V. Using the 0.18-mum N-well CMOS process, a third-order elliptic low-pass filter is implemented with the aid of the proposed OTA. The total harmonic distortion ( is -45 dB for 0.8-V peak-peak (Vpp) fully differential input signals. A dynamic range of 45 dB is obtained with the OTA's noise integrated over 1 MHz.